Handbook of research on nanoelectronic sensor modeling and applications - Ahmadi, Mohammad Taghi; Bin Ismail, Razali; Anwar, Sohail (Advances in computer and electrical engineering (ACEE), 2017)
This reference begins with an introduction of the fundamental concepts of nanoelectronic sensors, then proceeds to outline in great detail the concepts of nanoscale device modeling and nanoquantum fundamentals.